Laser-induced fabrication of highly branched Au@TiO2 nano-dendrites with excellent near-infrared absorption properties. Issue 86 (2nd September 2016) - Wang, Ziyu; Zhang, Hua; Xu, Linlin; Wang, Ziwei; Wang, Dameng; Liu, Xiangdong; Chen, Ming
Abstract : The highly branched Au@TiO2 nano-dendrites with excellent near-infrared absorption properties have been conveniently fabricated via a novel and effective laser-induced strategy. Abstract : In this report, highly branched Au@TiO2 nano-dendrites with a tailored surface topography have been conveniently fabricated via a novel and effective laser-induced strategy. The TiO2 nanospheres fabricated by laser ablation of the Ti target in H2 O2 solution are characterized by abundant oxygen vacancies (OVs) on the (110) surface. Then, the hydroxyl radical (OH − ) groups will be easily formed on the OVs in terms of water dissociation by UV laser irradiation of the TiO2 nano-spheres at the liquid interface. With the aid of OH − groups, the formation of Au@TiO2 nano-dendrites is based on the overgrowth of gold on the TiO2 nano-spheres through the reduction of HAuCl4 . The absorption spectra of Au@TiO2 nano-dendrites show that localized surface plasmon resonance (LSPR) peaks can be effectively modulated from the visible region (∼545 nm) to the near-infrared region (NIR ∼ 1090 nm). The as-prepared Au@TiO2 nano-dendrites with excellent NIR absorption properties have a promising potential for developing important novel sensors and super photo-catalysts.